Influence of pre-stroke dependency on safety and efficacy of endovascular therapy: A systematic review and meta-analysis - Zhao, Hengxiao; Bai, Xuesong; Li, Wei; Tian, Qiuyue; Wang, Wenjiao; Guo, Xiaofan; Feng, Yao; Duan, Linyan; Dmytriw, Adam A.; Patel, Aman B.; Yi, Tingyu; Cao, Wenbo; et al. (Frontiers in Neurology, 2022)
Background and Purpose: In the landmark trials studying endovascular thrombectomy (EVT), pre-stroke dependent (PSD) patients were generally excluded. This systematic review and meta-analysis aimed to compare the safety and efficacy of EVT between PSD and pre-stroke independent (PSI) patients. Methods: We searched CENTRAL, Embase and Ovid MEDLINE up to November 11, 2021 for studies assessing PSD and PSI patients, which were separately defined as pre-stroke mRS score＞2 or＞1, and ≤2 or ≤1 accordingly. Two authors extracted data and assessed the risk of bias. Meta-analysis was carried out using the random-effects model. Adjusted OR and 95% CI were used to estimate adjusted pool effects. Main outcomes included favorable outcome, successful recanalization, symptomatic intracranial hemorrhage and 90-day mortality. Results: 8004 records met the initial searching strategy and 10 studies were included in the final decision. Compared with PSImRS≤2, PSDmRS>2 had a lower favorable outcome (OR 0.51; 95% CI, 0.33-0.79) and higher 90-day mortality (OR 3.32; 95% CI 2.77-3.98). No significant difference was found in successful recanalization and sICH. After adjustment, only 90-day mortality (aOR 1.99; 95% CI, 1.58-2.49) remained significantly higher in PSDmRS>2. Compared with PSImRS≤1, PSDmRS>1 had lower 90-day mortality (OR, 3.10; 95% CI, 1.84-5.24). No significant difference was found regarding favorable outcome, successful recanalization and sICH. After adjustment, no significant difference was found in favorable outcome, but a higher rate of 90-day mortality (aOR, 2.13; 95% CI, 1.66-2.72) remained in PSDmRS>1. Conclusions: PSD does not innately influence the EVT outcomes regarding sICH and favorable outcome but may increase the risk of 90-day mortality. It seems reasonable to recommend EVT in PSD patients, pending future evidence.